2017
DOI: 10.21873/anticanres.11382
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Rituximab to Chemotherapy Reduced the Rate of Surgery for Gastric-DLBCL Without Increasing Early Mortality

Abstract: While rituximab appears to have significantly changed how surgery is utilized for patients with gDLBCL, early mortality was unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…However, no specific prognostic factors have been identified including the International Prognostic Index (IPI), because most patients were at low-or low-intermediate clinical risk and will be considered as low risk; other factors such as deep of invasion, tumor burden, lymph node invasion, and molecular profile have not been validated. [4][5][6][7][8][9][10][11][12][13][14][15] The use of combined treatments such as surgery, radiotherapy, and chemotherapy did not show any benefit in this setting of patients, [3][4][5][6][7][8][9][10][11] and the addition of rituximab is controversial; 4,5 in our experience, the addition of rituximab to CHOP chemotherapy does not improve outcome. 16 Some years ago, we performed a retrospective clinical study and found that patients with elevated serum levels of lactic dehydrogenase (LDH) and beta 2 microglobulin (B2M) (>2 of normal levels) have a worse prognosis, independent of other prognostic factors.…”
Section: Introductionmentioning
confidence: 85%
“…However, no specific prognostic factors have been identified including the International Prognostic Index (IPI), because most patients were at low-or low-intermediate clinical risk and will be considered as low risk; other factors such as deep of invasion, tumor burden, lymph node invasion, and molecular profile have not been validated. [4][5][6][7][8][9][10][11][12][13][14][15] The use of combined treatments such as surgery, radiotherapy, and chemotherapy did not show any benefit in this setting of patients, [3][4][5][6][7][8][9][10][11] and the addition of rituximab is controversial; 4,5 in our experience, the addition of rituximab to CHOP chemotherapy does not improve outcome. 16 Some years ago, we performed a retrospective clinical study and found that patients with elevated serum levels of lactic dehydrogenase (LDH) and beta 2 microglobulin (B2M) (>2 of normal levels) have a worse prognosis, independent of other prognostic factors.…”
Section: Introductionmentioning
confidence: 85%
“…23 Current studies have confirmed that the presence of Rituximab reduces the surgical rate of PG-DLBCL and do not increase the early mortality. 24 However, a SEER-based study of PG-DLBCL suggested that patient age, tumor stage, chemotherapy, and surgery were independent risk factors for long-term survival of PG-DLBCL patients, at the same time, the risk of death was high in the first two years, during which active follow-up should be pursued. 6 In our study, Chemotherapy and surgery are beneficial for overall survival of PsI-DLBCL, the internal validation based on SEER is also consistent.…”
Section: Discussionmentioning
confidence: 99%
“…The year of diagnosis was divided by decade 29 . The reason why we chose patients diagnosed from 1983 to 2015 was that they had complete Ann Arbor staging and surgical information 30 . Staging was defined according to Ann Arbor Stage of lymphoma.…”
Section: Methodsmentioning
confidence: 99%